2016
DOI: 10.1002/app.43311
|View full text |Cite
|
Sign up to set email alerts
|

Physical and antimicrobial properties of quinoa flour‐based films incorporated with essential oil

Abstract: Films of quinoa flour (Chenopodium quinoa, W) incorporated with oregano (Origanum vulgare L.) and thyme (Thymus vulgaris L.) essential oils (EOs) at 0.5%, 1%, and 2% p/p were prepared to examine their physical and mechanical properties and antimicrobial activity against Escherichia coli and Staphylococcus aureus. The type of EO was not significant for the physical and barrier parameters of the films. The increase in the EOs concentration led to an increase in the elongation at break, but decrease in the tensil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
4
9
0
2
Order By: Relevance
“…At alkaline pH, the increase of negatively charged groups that repeal each other could modify protein chain structure and intermolecular bonding [ 26 ]; this fact may produce thicker films. Chickpea film thickness was higher than those found in grass pea, amaranth, achira, red rice, pinhâo and lentil flour films [ 2 , 3 , 8 , 9 , 11 , 23 ], lower than in chia flour films [ 4 ] and similar to that of quinoa flour films [ 5 ]. Thickness was in the range of triticale, peanut and lentil protein films, and starch films [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At alkaline pH, the increase of negatively charged groups that repeal each other could modify protein chain structure and intermolecular bonding [ 26 ]; this fact may produce thicker films. Chickpea film thickness was higher than those found in grass pea, amaranth, achira, red rice, pinhâo and lentil flour films [ 2 , 3 , 8 , 9 , 11 , 23 ], lower than in chia flour films [ 4 ] and similar to that of quinoa flour films [ 5 ]. Thickness was in the range of triticale, peanut and lentil protein films, and starch films [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the use of flours for film preparation has gained importance due to the fact that they are natural and compatible mixtures of different components that can be easily obtained at lower cost than the mixtures of purified individual macromolecules. Films of flours from amaranth, red rice, achira, banana, quinoa, chia and pinhâo [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] have been produced and evaluated. Legume flours are also a good source of material for film formation due to their high content of starch and protein; some of them also contain a significant amount of lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Edible coating could be defined as a fine layer of biodegradable material, deposited on a food item. Its purpose is to inhibit or minimize the migration of humidity, oxygen, carbon dioxide and aromas, working as a semi-permeable barrier and flavouring, antioxidants and antimicrobial carrier, promoting the improvement of the product's texture and colouring and the increase of the products shelf life (Razavi et al, 2015;Antoniou et al, 2015;Treviño-Garza et al, 2015;Galus and Kadzińska, 2015;Pagno et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are slightly similar with those of Miranda et al [7] reported that the quinoa seeds cultivated in Korea, USA and Peru didn't have any antimicrobial effects against L. monocytogenes, While the dimeter of the growth inhibition zone of quinoa seeds cultivated in Korea, USA and Peru against E. coli were 7.04±0.11 mm, 7.35±0.35 mm and 7.35±0.25 mm, respectively which was lower than our recorded data. Antibacterial effect of the quinoa seeds against E. coli was also reported by Pagno et al (2016) [54]. Miranda et al (2014) [8] reported that the growth inhibition zones of the Ancovinto, Cancosa, Cahuil, Faro, Regalona, Villarrica ecotypes of the quinoa seeds against E. coli were 12.80±0.72 mm, 14.79±0.21 mm, 9.85±0.50 mm, 9.54±0.67 mm, 8.29±0.22 mm and 9.35±0.48 mm, respectively.…”
Section: Discussionmentioning
confidence: 73%